2020
DOI: 10.1186/s13049-020-00794-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation strategies prior to and during prehospital emergency anaesthesia in UK HEMS practice (PREOXY survey)

Abstract: Background Maintaining effective oxygenation throughout the process of Pre-Hospital Emergency Anaesthesia (PHEA) is critical. There are multiple strategies available to clinicians to oxygenate patients both prior to and during PHEA. The optimal pre-oxygenation technique remains unclear, and it is unknown what techniques are being used by United Kingdom Helicopter Emergency Medical Services (HEMS). This study aimed to determine the current pre- and peri-PHEA oxygenation strategies used by UK HEMS services. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…SIRBs are used for positive pressure ventilation in patients with insufficient breathing but also for preoxygenation of the spontaneously breathing. For patients undergoing anaesthesia with no access to ventilators or anaesthetic machines there are few practical alternatives to a SIRB [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIRBs are used for positive pressure ventilation in patients with insufficient breathing but also for preoxygenation of the spontaneously breathing. For patients undergoing anaesthesia with no access to ventilators or anaesthetic machines there are few practical alternatives to a SIRB [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for preoxygenation is a tight sealed mask connected to an anaesthetic machine, with close to an FiO 2 of 1.0 [1,2]. Outside of the OT and ICU the most common devices used for preoxygenation are SIRBs, freeflow oxygen masks, flow-dependent Mapelson systems or high-flow nasal cannulas [1][2][3]7]. The ability to manually ventilate apnoeic patients and limited oxygen supply typically makes a SIRB the preferred choice [3].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of these include thoracostomies to relieve a tension pneumothorax, the transfusion of blood products to treat ongoing blood loss, and pre-hospital emergency anesthesia (PHEA) to definitively manage the airway or to optimise ventilation. To prevent hypoxia during PHEA, patients are normally pre-oxygenated with a high FiO 2 and oxygen administration is continued thereafter [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Boulton et al . [ 13 ] reported that the most common preoxygenation stra-tegy from all UK Helicopter Emergency Medical Services was a BVM with a PEEP valve.…”
mentioning
confidence: 99%
“…BVMs facilitate positive pressure ventilation for apnoeic patients and are also commonly employed for preoxygenation in spontaneously breathing patients both during transport and in intensive care units (ICU) [11,12]. Boulton et al [13] reported that the most common preoxygenation strategy from all UK Helicopter Emergency Medical Services was a BVM with a PEEP valve.…”
mentioning
confidence: 99%